Shock wave interaction in a tee junction - Johnson, Richard Rushby (Department of Mechanical Engineering, 2016)
The problem was to determine the unsteady shock wave interaction at a tee junction, and to measure the transmitted shock strength. Two tee junctions of different cross-sectional shape were constructed, and instrumented with three piezoelectric pressure transducers and two hot wire anemometers. Tests were run in air for a Mach number range of 1.5 to 3.0, the different pressure ratios being obtained by varying the degree of vacuum in the driven section of the shock tube. A shock diffraction pattern for the tee is proposed and the transmitted shock strength is compared with the existing theories on shock diffraction around large corners.